2018
DOI: 10.3390/molecules23020470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the New Plant Growth Biostimulants Based on Amino Acids on Yield and Grain Quality of Winter Wheat

Abstract: Field and laboratory experiments were carried out in 2012–2013, aimed at evaluating the influence of new products stimulating plant growth based on amino acids on crop yield, characteristics of grain and content of macro- and micronutrients in winter wheat (Triticum aestivum L.). The tests included two formulations produced in cooperation with INTERMAG Co. (Olkusz, Poland)—AminoPrim and AminoHort, containing 15% and 20% amino acids, respectively, and 0.27% and 2.1% microelements, respectively. Field experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
88
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(116 citation statements)
references
References 17 publications
(30 reference statements)
5
88
1
3
Order By: Relevance
“…Biostimulants based on amino acids are produced through chemical synthesis from plant proteins, such as algae, maize or soyabean [9]. Another source is chemical or enzymatic hydrolysis of animals or plant proteins [5,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biostimulants based on amino acids are produced through chemical synthesis from plant proteins, such as algae, maize or soyabean [9]. Another source is chemical or enzymatic hydrolysis of animals or plant proteins [5,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Liuciatelli and coworkers indicated that a protein hydrolysate-based biostimulant derived from a legume and another product derived from tropical plant extracts altered the composition of the plant growth-promoting microbial population in lettuce [24]. Popko and coworkers demonstrated the potential of biostimulation of plants by foliar application of preparations based on keratin hydrolysates obtained from feathers [15]. The authors reported an increase in the yield of plant crops when compared to a control group and indicated that the increased efficiency of the tested biostimulants arose from the presence of micro-and macronutrients in hydrolysates of keratin protein.…”
Section: Introductionmentioning
confidence: 99%
“…Substances derived from amino acids (AA) constitute an important group of biostimulants. Their foliar application can improve acquisition of microelements (Kałużewicz et al 2018, Popko et al 2018. Modification of sugar content can be strengthened using commercial biostimulants such as Asahi SL and Kelpak SL (Zarzecka and Gugała 2018).…”
Section: Biostimulants and Symbiotic Microorganismsmentioning
confidence: 99%
“…Besides, they include growth regulators. The creation of complex preparations of microelements and growth regulators for foliage application is one of the main directions to optimize plant mineral nutrition [22]. In addition, modern liquid complex fertilizers with growthstimulating effect can play a significant role in crop management technologies, including soybeans [23].…”
Section: Introductionmentioning
confidence: 99%